2018
DOI: 10.1590/1678-5150-pvb-4821
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of bovine mastitis pathogens by MALDI-TOF Mass Spectrometry

Abstract: Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) has been shown to be an alternative method for identification of bacteria via their protein profile spectra, being able to identify bacteria at the genus, species and even at subspecies level. With the aim of large-scale identification of pathogens causing mastitis by this platform, a total of 305 isolates of bacteria identified from cows with subclinical mastitis were analyzed by conventional microbiological culture (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…For the present study, all cryopreserved bacteria were thawed and recultured on trypticase soy agar (BBL-Becton Dickinson and Co., Le Point de Claix, France) supplemented with 5% of bovine blood. Matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS) was used to confirm the isolates identification at the species level as previously described [30]. Only isolates identified as Strep .…”
Section: Methodsmentioning
confidence: 99%
“…For the present study, all cryopreserved bacteria were thawed and recultured on trypticase soy agar (BBL-Becton Dickinson and Co., Le Point de Claix, France) supplemented with 5% of bovine blood. Matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS) was used to confirm the isolates identification at the species level as previously described [30]. Only isolates identified as Strep .…”
Section: Methodsmentioning
confidence: 99%
“…Castro et al (2020) identified successfully the staphylococcal isolates from artisanal Minas cheeses in Brazil by MALDI-TOF MS. Horváth et al (2020) showed MALDI-TOF MS as a suitable for rapid and cost-effective identification of S. aureus among foodborne coagulase-positive Staphylococcus species in routine diagnostics. Braga et al (2018) identified S. aureus, S. chromogenes, S. epidermidis, and S. xylosus by MALDI TOF MS analysis of isolates detected from cows with subclinical mastitis, in order to broadly identify mastitis-causing pathogens. In addition, whole-cell MALDI-TOF MS has been demonstrated as a useful tool for rapid identification and classification of not only for Staphylococci, but also for a variety species of microorganisms both from dairy foods and other food groups (Murray, 2010).…”
Section: Spectral Inspection and Pca Of S Aureus And Other Staphylococcimentioning
confidence: 99%
“…Once the microbial samples are ready, the determination of species takes only a few minutes (Sauget et al, 2017). Microorganisms are identified using either cell extracts or intact cells in this proteomic assay (Manukumar & Umesha, 2017) which relies on the generation of unique protein profiles (protein fingerprints) captured from small amounts of bacterial colony material, followed by softwareassisted searching of an inbuilt proprietary database of wellcharacterized reference strains (Braga et al, 2018;Cameron et al, 2017;Sauget et al, 2017). Since it detects a large spectrum of proteins, the assay can discriminate between closely related species and also classify microorganisms at the subspecies level (Murray, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Brazil has the second largest dairy herd in the world and bovine mastitis is one of the main health problems affecting herds, with important economic losses in all dairy supply chain (Duarte et al 2020). This disease is characterized by an inflammation of the mammary gland, which directly affects its physiological function and cause symptoms such as: changes in color and consistency of milk, udder alterations, systemic disease and decreased yield (Kibebew 2017, Braga et al 2018.…”
Section: Introductionmentioning
confidence: 99%